Integration of Spiritual and Emotional Intelligence from the Perspective of Tafsîr al-Misbâh and Its Relevance to Modern Education - Zulfikar Fikri AlFasi; Abd Aziz; Ali Nurdin (The Future of Education Journal, 2026)
This study analyzes the integration of spiritual and emotional intelligence (SQ–EQ) in M. Quraish Shihab’s Tafsîr Al-Misbâh and its relevance to modern education. Modern education faces serious challenges due to the dominance of intellectual intelligence, which often neglects spiritual and emotional dimensions, resulting in academically capable learners who are fragile in character and mental resilience. The integration of SQ–EQ provides a holistic foundation for balanced modern education. Quraish Shihab’s concept of ulûl albâb a synthesis of dzikr (SQ), tafakkur (SQ), and tazkiyatun nafs (SQ-EQ) offers solutions to issues of globalization, moral crises, and the dichotomy of knowledge, leading to learners who are spiritually mature, emotionally stable, and endowed with strong moral integrity and social responsibility. The study formulates a three-stage integrative framework: (1) the axial stage (SQ) spiritual intelligence rooted in tawhîd, sincerity of intention, dhikr, and murâqabah as divine consciousness; (2) the driving stage (EQ) emotional intelligence developed through muhâsabah, mujâhadah, patience, gratitude, and istiqâmah in managing emotions; (3) the manifestation stage social ethics based on empathy, courteous communication, ishlâh, and ta‘âwun. The conceptualization of martabat al-nafs (nafs ammârah, mulhamah, muṭmainnah, râḍhiyah–marḍhiyyah) is identified as stages of emotional development aligned with increasing spiritual awareness. The findings include: (1) an SQ–EQ framework grounded in Tafsîr Al-Misbâh that integrates Qur’anic values with modern psychological theories of Goleman and Zohar–Marshall; (2) the formulation of love-based education and a purpose-driven curriculum rooted in tawhîd; and (3) concrete applications for the Kurikulum Merdeka and the Profil Pelajar Pancasila. This study employs a qualitative approach using library research and thematic exegesis. The primary source is Tafsîr Al-Misbâh, complemented by theories from Gardner, Zohar-Marshall, Goleman, Salovey-Mayer, and Abdullah Nashih Ulwan. Descriptive-analytic analysis is used to explore Qur’anic verses related to SQ-EQ and contextualize them with modern psychology to produce an applicable synthesis.